Literature and Creativity in an ELT Context - Alireza Zaker (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2016)
There is now a growing consensus among scientists and researchers that the mental and personal factors of individuals play a vital role in learning, especially learning English as a second language. Creativity, as one of these human factors, is believed to significantly affect L2 learning and life skills among human beings. Moreover, employing literature as the content of instruction in ELT is believed to provide EFL teachers and learners with numerous advantages, including higher levels of creativity. Based on this premise, this study suggests seven techniques which intend to promote creativity through employing literature in an EFL classroom. Following these techniques, some implementation concerns are stated in order to increase the chance of obtaining satisfactory results when employing these techniques. These concerns address the peculiarities of classroom environment, the role of cultural awareness, the importance of interaction, the significance of selecting a literary work, the appropriate feedback types, and motivation. The article concludes with some avenues for future research.